29th Digital Avionics Systems Conference 2010
DOI: 10.1109/dasc.2010.5655475
|View full text |Cite
|
Sign up to set email alerts
|

Sectorless ATM and advanced SESAR concepts: Complement not contradiction

Abstract: With SESAR (Single European Sky ATM Research) there is a program well on the way to developing and implementing advanced ATM (Air Traffic Management) concepts. Beyond the scope of the SESAR programme in the LRM2020 project there are investigations on sectorless ATM taking place, which would mean not an evolution but a revolution of current ATM. This discussion paper argues that sectorless ATM can not only be integrated and exploited within the SESAR innovations framework but also continues SESAR's shift toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Korn et al [3] and Pütz et al [4] reported on first proof-of-concept simulations. Further simulations were run to investigate different aspects of the concept; Biella et al [5] covered operational feasibility, while Birkmeier et al [6] explored the compatibility with SESAR (Single European Sky ATM Research), priority rules and avoidance maneuvers [7], mental models [8] and controller tasks [9].…”
Section: The Concept Of Sectorless Atmmentioning
confidence: 99%
“…Korn et al [3] and Pütz et al [4] reported on first proof-of-concept simulations. Further simulations were run to investigate different aspects of the concept; Biella et al [5] covered operational feasibility, while Birkmeier et al [6] explored the compatibility with SESAR (Single European Sky ATM Research), priority rules and avoidance maneuvers [7], mental models [8] and controller tasks [9].…”
Section: The Concept Of Sectorless Atmmentioning
confidence: 99%
“…To limit coordination via telephone, a complete and unambiguous set of flight rules has to be provided which regulates priority in all conflict situations. The set of rules that was used in our experiments is described in Birkmeier et al [5].…”
Section: The Concept Of Sectorless Atmmentioning
confidence: 99%
“…According to a prevailing opinion, this trend is unlikely to change in the future, although a number of contextual factors, such as political climate, economy, environmental issues, safety issues and security issues may affect its actual rate. Further, according to the 'Free Flight' and the '4D Trajectory Management' concepts, different types of aircraft, such as manned, unmanned, and autonomous aircraft, as well as all kinds of rotorcrafts, will operate simultaneously in a 'structure-less' and 'time based' environment [1][2] allowing for much more direct and continuous trajectories to be used. Also, brand new airspace designs, possibly dynamic, may be required.…”
Section: Introductionmentioning
confidence: 99%